Exploring the effect of neighboring land cover pattern on land surface temperature of central building objects. (January 2016) - Feng, Xin; Myint, Soe W.
Abstract: Increased temperatures in urban landscapes bring about a variety of problems and exacerbating thermal discomfort. Many studies have focused on detecting the effects of land cover patterns, including composition and configuration, on land surface temperature (LST) using remote sensing images. This study focused on distinct land cover feature, buildings, in center of Beijing, China, exploring the relationship between the LST of central building objects and land cover patterns in their neighboring areas. Classifying buildings into three groups (low-rise, mid-rise, and high-rise) allowed the effects of neighboring land cover patterns on building LST to be analyzed independently. We found that the composition of land cover features has a stronger impact on low-rise building LST than mid-rise and high-rise building LST. Moreover, low-rise building LST is highly related to the composition of neighboring vegetation and pavement. This relationship is limited for mid-rise buildings and high-rise buildings. Finally, LST can be mitigated not only by balancing the amount of vegetation and buildings, but, for low-rise buildings, can also be mitigated by optimizing their spatial configuration. This study enhances our understanding of the degree to which LST of different height buildings are affected by neighboring land cover patterns. In addition, important insights can be provided to urban planners on how to mitigate the impact of urbanization on UHI through urban design and vegetation management. Highlights: The relationships between central LST & neighboring land cover pattern vary for different heights buildings. The composition of most land cover features has a stronger impact on LST of low-rise building than LST of other buildings. The composition of mid-rise and high-rise buildings contributes a great proportion of central high-rise buildings' LST. LST can be mitigated not only by balancing the composition of land cover features, but by optimizing spatial configuration.